The Role of Digital Communication in Enhancing Collaboration in the Information Technology Industry - Jaizul , Alim; Lianingsih, Nestia (International Journal of Linguistics, Communication, and Broadcasting, 2025)
This study examines the role of digital communication tools in enhancing team productivity and collaboration within the information technology (IT) industry. With the rapid advancement of technology and the increased need for remote work, digital tools have become essential for facilitating communication and collaboration, particularly in geographically dispersed teams. The study employs a mixed-methods approach, combining quantitative data from a survey of 200 IT professionals and qualitative insights from in-depth interviews with 10 team leaders. The results indicate that digital tools significantly improve productivity (87%), ease of communication between teams (90%), and support collaboration (92%). However, 60% of respondents reported experiencing digital fatigue, highlighting the psychological toll of excessive digital communication. Key challenges identified include an overwhelming number of notifications, insufficient training, and tight meeting schedules. To address these challenges, respondents suggested implementing flexible policies, regular training, and reducing notifications during work hours. The findings emphasize the importance of optimizing the use of digital tools while balancing technology with interpersonal connections to foster better team cohesion and well-being. This research provides valuable insights for IT companies and other sectors adopting digital communication tools, offering practical strategies to enhance efficiency while mitigating potential drawbacks such as digital fatigue.